Moderasi Beragama melalui Film Animasi: Peluang dan Tantangan pada Generasi Digital - Icol Dianto (NALAR, 2021)
This research aims to examine the opportunities and challenges in the use of animated films as a medium to instill religious moderation in Indonesia. The method used in this research is literature research by analyzing the results of research, legal text, and information related to religious moderation and animated film media. The results found that Indonesia has a great opportunity to utilize information and multimedia technology, especially in producing animated films. The opportunity can be detailed that Indonesia has a technology infrastructure that is almost evenly distributed in all corners of the country, rich in local culture and wisdom, and has reliable human resources in the field of multimedia technology. On the other hand, the rapid flow of information containing religious conservatism through online media and television media dominated by violence is a challenge for the Government of Indonesia. The ideology of religious moderation must be packaged creatively and attract the interest of the audience. Thus, understand the moderation of religion that is expected to be ingrained in the life of the nation and state.Keyword : Religious Moderation; Animated Film; Religious Conservatism